Hubungan Kadar Magnesium dan Kebugaran dengan Tingkat Stress pada Pengemudi Ojek Online - Chondro, Fransisca; Margo, Eveline; Handayani, Astri; Chudri, Juni (Fakultas Kedokteran Universitas Trisakti, 2024)
Background Most countries around the world suffered from the high-level transmission COVID-19. Thus, the government enforced a policy for the citizens to work from home. These restrictions impact the mental health of the citizens, and the prevalence of stress increases. Some of the factors that affect stress are magnesium intake and physical fitness. The study found that magnesium levels and fitness are correlated with stress levels. But some studies got different results. Thus, learning more about the relationship between magnesium level, fitness, and stress level is necessary. Methods This is a cross-sectional design study with consecutive non-random sampling methods. This study involving online drivers was held in Kampus B, Fakultas Kedokteran Universitas Trisakti, in September 2022. The inclusion criteria are aged 15-64 years, willing to sign the informed consent, can communicate well, while the exclusion criteria are in the therapy of anti-depressant or anti-anxiety drugs, and has a history of heart attack within one month. Results Based on the data, it can be concluded that most respondents are male, from the middle-aged group, and suffer from obesity, and about 50% of the respondents suffer from high blood pressure. Most respondents have normal blood-magnesium levels and medium levels of stress, while all the respondents have poor or very poor physical fitness. On the Chi-square test between age, sex, body mass index, blood pressure, physical fitness and stress level, the level of significance consecutively are 0.645; 0.208; 0.364; 0.451 and 1.000. While on the Fisher test, the significance level between blood magnesium level and stress level is 0.099. Conclusions Based on the bivariate test, it can be concluded that there is no significant relationship between age, sex, body mass index, blood pressure, physical fitness and blood magnesium level with the stress level.